Complexity of understanding the role of dietary and erythrocyte docosahexaenoic acid (DHA) on the cognitive performance of school-age children. Issue 7 (16th June 2022) - Mulder, Kelly A; Dyer, Roger A; Elango, Rajavel; Innis, Sheila M
ABSTRACT: Background: Early childhood is a period of rapid brain development, with increases in synapses rich in the omega-3 (ω-3) fatty acid, DHA (22:6ω-3) continuing well beyond infancy. Despite the importance of DHA to neural phospholipids, the requirement of dietary DHA for neurodevelopment remains unclear. Objectives: The aim was to assess the dietary DHA and DHA status of young children, and determine the association with cognitive performance. Methods: This was a cross-sectional study of healthy children (5–6 y), some of whom were enrolled in a follow-up of a clinical trial (NCT00620672). Dietary intake data ( n  = 285) were assessed with a food-frequency questionnaire (FFQ) and three 24-h recalls. Family characteristics were collected by questionnaire, and anthropometric data measured. Venous blood was collected, cognitive performance assessed using several age-appropriate tools including the Kaufman Assessment Battery for Children. The relation between dietary DHA, RBC DHA, and child neurodevelopment test scores was determined using Pearson's correlation or Spearman's rho, and quintiles of test scores compared by Mann–Whitney U test. Results: Child DHA intakes were highly variable, with a stronger association between RBC DHA and DHA intake assessed by FFQ (rho = 0.383, P  < 0.001) compared with one or three 24-h recalls. Observed ethnic differences in DHA intake status as well as neurodevelopmental test scores led to analysis of the association between DHA intake and status with neurodevelopment test scores for White children only ( n  = 190). Child RBC DHA status was associated with neurodevelopment test scores, including language (rho = 0.211, P  = 0.009) and short-term memory (rho = 0.187, P  = 0.019), but only short-term memory was associated with dietary DHA (rho = 0.221, P  = 0.003). Conclusions: Child RBC DHA but not dietary DHA was associated with multiple tests of cognitive performance. In addition, DHA intake was only moderately associated with RBC DHA, raising complex questions on the relation between diet, DHA transfer to membrane lipids, and neural function. Abstract : In children aged 5–6 y red blood cell (RBC) docosahexanoic acid (DHA), but not dietary intake of DHA, is associated with multiple tests of cognitive performance, emphasizing the complexity of DHA metabolism.